'Double chiral' new members of calixsalen family. Issue 10 (15th October 2017) - Petryk, Małgorzata; Janiak, Agnieszka; Kwit, Marcin
Graphical abstract: Abstract: Synthesis and X-ray diffraction studies on the first examples of 'double chiral' calixsalens are presented. In these molecules, one can clearly distinguish two chiral zones. The first one is made by the macrocycle base, whereas the second chiral zone is set up of the additional chirality elements in the tail of the molecule. The 'double chiral' calixsalens are formed through cyclocondensation between chiral vicinal diamine of trans -1, 2-diaminocyclohexane type and chiral C-5 substituted 2-hydroxyisophthalaldehyde derivatives. The absolute configuration of the dialdehyde did not affect the yield of the macrocyclization reaction. The presence of secondary amides in the tail part of the macrocycle leads to formation of hydrogen bonding network in the solid state, while sterical hindrance preserve interdigitation, thus, 'double chiral' calixsalens do not form aggregates typical for other calixsalens. Abstract : ( R )-3′, 5′-Diformyl-4′-hydroxy- N -(1-phenylethyl)-[1, 1′-biphenyl]-4-carboxamide: [ α ]D 20 = −94.6 ( c 1, methanol) Source of chirality: chiral precursor Absolute configuration: ( R ) Abstract : ( R )- N -(1-Cyclohexylethyl)-3′, 5′-diformyl-4′-hydroxy-[1, 1′-biphenyl]-4-carboxamide: [ α ]D 20 = −38.5 ( c 1, methanol) Source of chirality: chiral precursor Absolute configuration: ( R ) Abstract : 4, 4′, 4″-((2 E, 5 E, 11 E, 14 E, 17 E )-12, 72, 132-Trihydroxy-3, 5, 9, 11, 15, 17-hexaaza-1, 7, 13(1, 3)-tribenzena-4, 10, 16(1, 2)-tricyclohexanacyclooctadecaphane-2, 5, 8, 11, 14, 17-hexaene-15, 75, 135-triyl)tris( N -(( R )-1-phenylethyl)benzamide): [ α ]D 20 = −306.1 ( c 1, chloroform) Source of chirality: chiral precursor Absolute configuration: (all- R ) Abstract : ( R )-4-Bromo- N -(1-cyclohexylethyl)benzamide: [ α ]D 20 = −28.6 ( c 1, methanol) Source of chirality: chiral precursor Absolute configuration: ( R ) Abstract : ( R )-(4-((1-Phenylethyl)carbamoyl)phenyl)boronic acid: [ α ]D 20 = −36.4 ( c 1, methanol) Source of chirality: chiral precursor Absolute configuration: ( R ) Abstract : ( R )-(4-((1-Cyclohexylethyl)carbamoyl)phenyl)boronic acid: [ α ]D 20 = −30.0 ( c 1, methanol) Source of chirality: chiral precursor Absolute configuration: ( R )